Schools’ character education values and students’ mathematics learning achievement: A meta-analysis - Khadijah Khadijah; Indah Suciati; Khaerani Khaerani; Abdul Manaf; Sutamrin Sutamrin (LPMPP Universitas Negeri Yogyakarta, 2021)
Character education plays a critical role in all aspects of life and thus, it has been widely-adopted in schools. An indication of its success can be reflected in the student learning achievement. The purpose of the study was to determine the effect size of the relationship between character education values and mathematics learning achievement, with a meta-analysis study. In this research, character education value is the independent variable while mathematics learning achievement is the dependent one. The data were obtained from the results of online database search at Google Scholar from 2012-2019. Based on the search, 16 research publications met the criteria determined based on rigorous screening. The data were analyzed using a quantitative meta-analysis approach, specifically correlation meta-analysis. The results show that there was a significant relationship between character education values and students’ mathematics learning achievement. The effect size value was in the moderate effect category. The findings are in line with those of previous studies investigating this relationship and thus, strengthen the theory about the factors that influence mathematics learning achievement. In addition, these findings suggest five-character education values that teachers can provide to improve students’ mathematics learning achievement.